Alone in the back office: the isolation of those who care to support public services. (August 2015) - Butler, Clare; Doherty, Anne Marie; Finniear, Jocelyn; Hill, Stephen
Prior research suggests that it is through providing direct support to citizens that public servants gain a source of meaning in their work; and affirm their public service identities. This article explores how employees who work in a public service support function and receive little, if any, direct feedback from citizens may maintain their public service identity during their back office work. The study finds, against much previous empirical research, that these back office employees achieve positive identity affirmation through bureaucratic work. The findings also show that they affirm their caring and community focused public service identity by noting their superiority in this regard when compared with colleagues. However, this augmented self-narrative results in many experiencing feelings of isolation. The article discusses how these findings extend the understanding of identity affirmation among back office public servants and may improve our ability to effectively support these workers.